2019
DOI: 10.32892/jmri.185
|View full text |Cite
|
Sign up to set email alerts
|

Race, Educational Attainment, and E-Cigarette Use

Abstract: Background: Although higher educational attainment lowers high-risk behaviors such as substance use, according to the Minorities’ Diminished Returns theory, the effect of educational attainment may be smaller for Blacks than Whites. Aims: To explore the racial differences in the link between educational attainment and electronic cigarettes (e-cigarettes). Methods: We used the Health Information National Trends Survey (HINTS) data. This national survey was conducted in 2017 and included 2,277 Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 64 publications
3
57
0
Order By: Relevance
“…The observation that as income increases, the psychological well-being of middle-aged and older adults improves, but less for immigrants than non-immigrants, is an extension of previous literature on MDRs 21,22 of income, [23][24][25][26][27] educational attainment, 36 occupation, 29,30 and marital status 46 on a wide range of mental health outcomes, including psychological distress, 54 depression, 24,55 suicide, 31 and anxiety. 46 These MDRs go beyond physical health outcomes and extend to behavioral outcomes such as vaping, 33 smoking, 35,42,44,56,57 drinking, 34,58 diet, 59 and exercise. 11 Finally, MDRs are seen for physical health outcomes such as obesity, 36,37 self-rated health, 23,32,54 CMCs, 25,26,38 disability, 60 and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that as income increases, the psychological well-being of middle-aged and older adults improves, but less for immigrants than non-immigrants, is an extension of previous literature on MDRs 21,22 of income, [23][24][25][26][27] educational attainment, 36 occupation, 29,30 and marital status 46 on a wide range of mental health outcomes, including psychological distress, 54 depression, 24,55 suicide, 31 and anxiety. 46 These MDRs go beyond physical health outcomes and extend to behavioral outcomes such as vaping, 33 smoking, 35,42,44,56,57 drinking, 34,58 diet, 59 and exercise. 11 Finally, MDRs are seen for physical health outcomes such as obesity, 36,37 self-rated health, 23,32,54 CMCs, 25,26,38 disability, 60 and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown disproportionately high risk of tobacco use in highly educated and high-socioeconomic status Hispanic and African American individuals, across tobacco products. 16,17,21,67 Highly educated Hispanic and African American individuals are also exposed to higher levels of secondhand tobacco smoke inside their homes 68 and at work 26 compared with white individuals. Thus, highly educated racial/ethnic minority groups remain at high risk of chronic medical conditions, such as chronic obstructive pulmonary disease, 69 asthma, 70 and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The results may be due to the fact that highly educated and high-income Blacks and Hispanics smoke cigarette (Assari & Mistry, 2018; and vape e-cigarette (Assari, Mistry, & Bazargan, 2020) more than what is expected based on their SES. Such more than expected behavioral risk profile of high-SES…”
Section: Ses) Declinesmentioning
confidence: 86%
“…In a study, highly educated Blacks and Hispanics were found to be exposed to high levels of second-hand smoke exposure . In another study, highly educated and high-income Blacks and Hispanics were more likely to drink alcohol (Assari, Farokhnia, & Mistry, 2019;, smoke cigarette (Assari & Mistry, 2018;Shervin & Ritesh, 2019), and vape e-cigarette (Assari, Mistry, & Bazargan, 2020). This is probably why highly educated and high-income Blacks and Hispanics may be at higher risk of chronic obstructive pulmonary disease (COPD) (Assari, Caldwell, & Bazargan, 2019) and asthma (Assari & Moghani Lankarani, 2018), compared to highly educated non-Hispanic…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation